Party guests or party crashers? Non-members’ political engagement across party organizations - Giulia Sandri; Felix-Christopher von Nostitz (QOE-IJES)
Over the past decade, many parties have created new possibilities for affiliating and involving citizens, often rivalling the classic conception of party membership. So far, the existing literature has mainly focused on classifying these new and different types of affiliates. However, little attention has been paid to what these “non-full-membership” options imply in terms of formal rights and obligations. We explore here the opportunities that parties offer to non-members to participate and get involved in intra-party activities and we contrast them with the rights and obligations of full, fee-paying, traditional members. This article addresses this gap based on an original database consisting of membership rules in 68 parties in 13 established democracies. We not only map the current landscape of rules managing the involvement of non-members within parties, but also explore potential factors- party family and size- explaining the variation across parties. We find a strong association between party family and the range of possibilities for non-members’ involvement with parties on the left and environmental parties providing more space for the participation of non-members. We also find that smaller parties tend to involve more non-full-members by allocating more rights to them. Our findings and new database provide a first step for future research to study the regulation of the involvement of non-members in intra-party activities, what determines it, and how it affects the traditional concept of party membership and societal linkage.